Local therapy in non-metastatic primary Ewing sarcoma of the mandible and maxilla in children. Issue 8 (August 2016) - Qureshi, S.S.; Bhagat, M.; Laskar, S.; Kembhavi, S.; Vora, T.; Ramadwar, M.; Chinnaswamy, G.; Prasad, M.; Khanna, N.; Shah, S.; Talole, S.
Abstract: Ewing sarcoma (ES) of the jaw bones comprises a small fraction of ES at all sites. Due to their rarity, a specific policy for local treatment is lacking. The aim of this study was to evaluate the local therapy for ES and recommend measures to individualize treatment options. Patients with primary non-metastatic ES of the jaw bones treated between August 2005 and February 2015 were analyzed. All patients received primary induction chemotherapy, following which lesions amenable to resection based on specific radiological criteria were resected; those with unresectable lesions were offered definitive radiotherapy. The maxilla was the primary site in 13 patients and the mandible in eight. The median age of patients was 11.6 years (range 5–17 years). Overall, surgery was performed in 17 patients and definitive radiotherapy was used in four patients. Postoperative radiotherapy was administered to 12 patients and was avoided in five patients with 100% tumour necrosis. The 3-year overall survival, event-free survival, and local control were 68.1%, 63.6%, and 80.2%, respectively. Mandible primary and a histological response to chemotherapy were significant prognostic factors. The stratification of patients based on radiological criteria aids in selecting local therapy. In eligible patients, surgery with contemporary reconstruction results in optimal oncological and functional outcomes. Surgery also has the added advantage of identifying patients who may not need radiotherapy.